KNOWLEDGE‐BUILDING IN ASIAN PUBLIC ADMINISTRATION: AN INTRODUCTORY OVERVIEW. (18th September 2013) - Haque, M. Shamsul; Turner, Mark
SUMMARY: In recent years, the re‐emergence of Asia as a global power coincided with the proliferation of Asian studies in diverse disciplines and institutions worldwide. However, although the state and its administrative apparatus have been directly instrumental to this Asian success story, there is still inadequate research on the role of public administration in Asia. Thus, there is a need for exploring major issues related to research and knowledge building in Asian public administration. Copyright © 2013 John Wiley & Sons, Ltd.